Efek minuman kombinasi maltodekstrin dan vitamin C terhadap VO2maks atlet sepak bola - Desty Ervira Puspaningtyas; Toto Sudargo; Arta Farmawati (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2015)
Background: VO2max is one of win determiner in a game. Athletes receive training to improve technical skills, tactical skills, and physiology functions that can support the improvement of VO2max, so they can improve their achievement. Maltodextrin and vitamin C can be used as an ingredient for beverage products which can improve VO2max.Objective: To assess the effect of maltodextrin and vitamin C combination drink on VO2max in soccer athletes.Method: Type of this study was experimental design with the same subject design. The study was conducted from January 2014 until June 2014 at Culinary Laboratory Universitas Gadjah Mada (UGM) and Stadium of Universitas Negeri Yogyakarta (UNY). Subjects of this study were 14 soccer players coming from Universitas Negeri Yogyakarta (UNY). Every subject had to fulfill the inclusion and exclusion criteria, and the subjects were chosen by purposive sampling. In the first treatment, subjects received the combination drink―a drink with a composition 15% of maltodextrin and 250 mg of vitamin C in 300 mL. After 6 days washout period, subjects received 300 mL plain water. Drinks were given 30 minutes before VO2max test. VO2max test method used in this study was yo-yo intermittent recovery test level 2 (IR-2).Results: VO2max when subjects consumed maltodextrin and vitamin C combination drink was significantly lower than VO2max when athletes consumed plain water (p=0,0000).Conclusion: Maltodextrin and vitamin C combination drink was less effective than plain water to enhance VO2max.